Hotel's Strict Restriction of Outside Meals Arrangement during Pandemic Covid-19: An Evaluative Study - Ni Kadek Indri Meliati; I Gusti Ayu Putu Wita Indrayani; Putu Gede Eka Darmaputra (JURNAL BISNIS HOSPITALITI, 2022)
The implementation of global health protocols is carried out by hotel management with the aim of limiting the spread of the virus; one of them is CHSE certification. The purpose of this study was to evaluate the strict prohibition or restriction on bringing food and drinks from outside the hotel during the pandemic. Rules whose original purpose is to secure guest safety essentially have an impact on increasing complaints and negative reviews from hotel guests. Sources of data in this study are primary data, namely the results of interviews with Front Office Staff, Front Office Supervisors and Front Office Managers, as well as secondary data obtained from online travel agents in the form of guest complaints. The analytical technique used is narrative analysis where the data is presented in the form of a narrative or story. In this study, it was analyzed using four evaluation indicators, namely: context evaluation, input evaluation, process evaluation, and outcome evaluation. The results of this study indicate that the strict restriction policy on bringing food and drinks from outside the hotel during the pandemic has not been in accordance with its objectives, so the program does not run optimally and needs to be discontinued.